Struktur Mikroanatomi Ren Ayam (Gallus Sp.) karena Pengaruh Pemberian Kunyit Putih (Curcuma Zedoaria) - Muliani, Hirawati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
This research was aimed to know about the effect of zedoary on chicken’s kidney microanatomy structure. Twenty female broiler chickens was acclimated during 3 weeks. Those chickens then allotted into 5 groups of treatment, with 4 replications in each group. The treatments were 0 ppm; 500 ppm; 1000 ppm; 1500 ppm; and 2000 ppm zedoary powder on drinking water during 3 weeks. Main parameter observed were height of proximal convoluted tubule epithelial cell, height of distal convoluted tubule epithelial cell, and glomerulus structure change. Supported parameters were consumption of drinking water, and weight of chicken’s kidney at the end of treatment. Quantitative data was analyzed by varians analysis with Completely Random Design and Least Significant Difference Test. The result showed that zedoary affect microanatomy structure of chicken’s kidney.